Syntax Score and Major Adverse Cardiac Events in Patients with Suspected Coronary Artery Disease: Results from a Cohort Study in a University-Affiliated Hospital in Southern Brazil - Fuchs,Felipe C. (2016)
Abstract Background: The importance of coronary anatomy in predicting cardiovascular events is well known. The use of traditional anatomical scores in routine angiography, however, has not been incorporated to clinical practice. SYNTAX score (SXscore) is a scoring system that estimates the anatomical extent of coronary artery disease (CAD). Its ability to predict outcomes based on a baseline diagnostic angiography has not been tested to date. Objective: To evaluate the performance of the SXscore in predicting major adverse cardiac events (MACE) in patients referred for diagnostic angiography. Methods: Prospective cohort of 895 patients with suspected CAD referred for elective diagnostic coronary angiography from 2008 to 2011, at a university-affiliated hospital in Brazil. They had their SXscores calculated and were stratified in three categories: no significant CAD (n = 495), SXscoreLOW-INTERMEDIATE: < 23 (n = 346), and SXscoreHIGH: ≥ 23 (n = 54). Primary outcome was a composite of cardiac death, myocardial infarction, and late revascularization. Secondary endpoints were the components of MACE and death from any cause. Results: On average, patients were followed up for 1.8 ± 1.4 years. The primary outcome occurred in 2.2%, 15.3%, and 20.4% in groups with no significant CAD, SXscoreLOW-INTERMEDIATE, and SXscoreHIGH, respectively (p < 0.001). All-cause death was significantly higher in the SXscoreHIGH compared with the 'no significant CAD' group, 16.7% and 3.8% (p < 0.001), respectively. After adjustment for confounding factors, all outcomes remained associated with the SXscore. Conclusions: SXscore independently predicts MACE in patients submitted to diagnostic coronary angiography. Its routine use in this setting could identify patients with worse prognosis.